Effects of Exercise Domain and Intensity on Sleep in Women and Men with Overweight and Obesity - Jonas Salling Quist; Mads Rosenkilde; Anne Sofie Gram; Martin Bæk Blond; Daniel Holm-Petersen; Mads Fiil Hjorth; Bente Stallknecht; Anders Sjödin (Journal of Obesity)
Inadequate sleep is associated with cardiometabolic risk and adiposity. Exercise has been suggested as an efficient strategy to improve sleep; however, the effects of different types of exercise on sleep in individuals with overweight and obesity are not well understood. We examined effects of active commuting and leisure-time exercise on sleep in individuals with overweight or obesity. 130 physically inactive adults (20–45 years) with overweight or class 1 obesity (body mass index: 25–35 kg/m2) were randomized to 6 months of habitual lifestyle (CON, n = 18), active commuting by bike (BIKE, n = 35), or leisure-time exercise of moderate intensity (MOD, 50% VO2peak-reserve, n = 39) or vigorous intensity (VIG, 70% VO2peak-reserve, n = 38), 5 days/week. Sleep was assessed from 7-day/night accelerometry and questionnaires at baseline, 3 months, and 6 months. 92 participants were included in a per protocol analysis. At 3 months, sleep duration was longer in VIG (29 min/night [3; 55] (mean [95% CI]), p=0.03) but not in BIKE and MOD (p≥0.11) compared with CON and was not different between groups at 6 months (p≥0.36 vs. CON). At 6 months, sleep duration variability was lower in MOD (−31% [−50; −3], p=0.03) and numerically lower in VIG (−28% [−49; 1], p=0.06) relative to CON but was unchanged in BIKE (p=0.17 vs. CON). The effects were, however, primarily attributable to shorter and more irregular sleep in CON over time. Our findings suggest that effects of exercise on sleep in individuals with overweight and obesity may be restricted to leisure-time exercise with a short-term effect on sleep duration after vigorous intensity exercise (3 months) but a more regular sleep pattern after 6 months of moderate and vigorous intensity exercise compared with physically inactive controls. This trial was registered at clinicaltrials.gov with ID NCT01962259.